2011
DOI: 10.1590/s0103-90162011000500015
|View full text |Cite
|
Sign up to set email alerts
|

Solubilisation of inorganic phosphates by inoculant strains from tropical legumes

Abstract: Microbial solubilisation of low soluble inorganic phosphates is an important process contributing for the phosphorus available to plants in tropical soils. This study evaluates the ability of inoculant strains for tropical legumes to solubilise inorganic phosphates of low solubility that are found in tropical soils. Seven strains of Leguminosae nodulating bacteria (LNB) were compared with one another and with a non-nodulating positive control, Burkholderia cepacia (LMG 1222 T 3 . In liquid GELP medium, LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 29 publications
5
46
1
3
Order By: Relevance
“…The formation of a solubilization halo was not detected in solid medium containing AlPO 4 . This result differed from other AlPO 4 solubilization studies in which several authors detected solubilization halos in solid media containing P precipitated with Al (Hara and Oliveira, 2005;Marra et al, 2011Marra et al, , 2012Oliveira-Longatti et al, 2014). However, it is important to note that the media and the sources of P were different from these studies.…”
Section: Discussioncontrasting
confidence: 95%
“…The formation of a solubilization halo was not detected in solid medium containing AlPO 4 . This result differed from other AlPO 4 solubilization studies in which several authors detected solubilization halos in solid media containing P precipitated with Al (Hara and Oliveira, 2005;Marra et al, 2011Marra et al, , 2012Oliveira-Longatti et al, 2014). However, it is important to note that the media and the sources of P were different from these studies.…”
Section: Discussioncontrasting
confidence: 95%
“…However, the soil solution pH did not change after the experiment for any of the treatments in the present study. This result is consistent with those of Marra et al, (2011), who demonstrated that the solubilisation of insoluble inorganic phosphates is not always associated with the lowering of pH. We found the highest levels of available P in the soil solutions treated with BRP and the lowest levels in the soil solutions treated with SP.…”
Section: Discussionsupporting
confidence: 93%
“…The genus Burkholderia can benefit plant growth in several ways, such as in siderophore production and phosphate solubilization (Vial et al, 2007;Collavino et al, 2010;Marra et al, 2011;Mathew et al, 2014). This genus represented 46 % of the sequenced isolates, occurring in all types of vegetation.…”
Section: Discussionmentioning
confidence: 99%